Voltage Regulation in a Radial Microgrid with High RES Penetration: Approach-Optimum DVR Control - Gour, R.; Verma, V. (Engineering, Technology & Applied Science Research, 2022)
Increasing installation of Renewable Energy Sources (RESs) in microgrids and distribution system feeders benefits the power system in many ways, such as increasing power availability and reliability, but they also cause various power quality issues, such as overvoltage and undervoltage, due to their intermittent nature. The sensitive loads, such as Constant Power Load (CPL), are affected by these voltage fluctuations. The approach proposed in this paper is to install a Dynamic Voltage Regulators (DVR) adjacent to the RES to suppress the voltage issue caused by it while leaving the sensitive load operation unharmed. The proposed concept is duly endorsed with analysis and simulations in MATLAB/Simulink environment.